Interpersonal relationship and self-acceptance on emotional intelligence and mental health of college students - Lezheng Niu; Yongcheng Yao; Nursyuhaidah Mohd Kadri; Farooqi Sharifullah (International Journal of Public Health Science (IJPHS), 2022)
The study aimed to explore the role of interpersonal relationship and self-acceptance as potential moderator of the relationship between emotional intelligence and mental health of college students in China. The online survey platform “Questionnaire Star” was conducted among 367 undergraduates. The questionnaires of self-rated health measurement scale, emotional intelligence scale, interpersonal relationship assessment scale, and self-acceptance questionnaire was used for questionnaire survey and analysis. The self-rated health status was positively correlated with emotional intelligence and self-acceptance (r=0.541, 0.598, p<0.01), and negatively correlated with interpersonal relationships (r=-0.609, p<0.01). Further analysis using multivariate regression found that the interaction between emotional intelligence, interpersonal relationship and self-acceptance is statistically significant (β=-0.02, p<0.05), with the independent effect on health status is 0.7% (ΔR2=0.006), and the negative effect of interpersonal relationship was the biggest (β=-2.691). Conclusion This study highlighted the psychological protection ability of self-rated health, which is influenced by interpersonal relationship, self-acceptance and emotional intelligence. Interpersonal relationship is the main factor that affects the emotional intelligence on self-rated health. Under the same conditions of emotional intelligence and self-acceptance, college students with good interpersonal relationship have better self-measured health status.